EVA graphene composite film and preparation method thereof

By aminating modification of graphene oxide and titanate modification, combined with the hot pressing film formation technology of graphene and EVA, an EVA graphene composite film with high water vapor barrier and electrical resistance was prepared, which solved the problems of low strength and poor weather resistance of EVA films, and achieved efficient water vapor resistance and electrical resistance.

CN119526876AActive Publication Date: 2025-02-28CHANGZHOU BEMATE HOME TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411665273.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-28
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

The EVA film has low strength, high water vapor transmission and water absorption, and poor weather resistance, which limits its application in barrier properties.

Method used

Through the aminization modification of graphene oxide and the modification of titanate, combined with the hot pressing film formation technology of graphene and EVA, an EVA graphene composite film was prepared. The method includes in-situ grafting of graphene oxide and EVA, forming a physical barrier layer of graphene sheets, and hydrophobic modification of titanate.

Benefits of technology

It significantly reduces the water vapor transmittance of EVA film, enhances its resistance performance, and is simple in process and low in cost, suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005144435800000091
    Figure BDA0005144435800000091
  • Figure BDA0005144435800000101
    Figure BDA0005144435800000101
Patent Text Reader

Abstract

The invention discloses an EVA graphene composite film and a preparation method thereof, and belongs to the technical field of functional polymer composite materials. The preparation method comprises the following steps: adding organic amine into a graphene oxide dispersion liquid, reacting for a period of time, washing, and drying to obtain the modified graphene oxide. Organic matter intercalation is used for modifying titanate to obtain modified titanate. EVA, graphene and the modified titanate are mixed and subjected to hot pressing to form a film, and the EVA graphene outer film is obtained. Feeding EVA, the modified graphene oxide and an initiator into an open mill for coarse mixing; after open milling is completed, the mixture is put into a double-screw extruder to be subjected to blending extrusion and then subjected to hot pressing to form a film, and the EVA graphene inner film is obtained. And sequentially overlapping the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film, and carrying out hot-pressing compounding to obtain the EVA graphene composite film. The composite film obtained by the preparation method has water vapor resistance and electricity resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of functional polymer composite materials, and in particular to an EVA graphene composite film and a preparation method thereof. Background Art

[0002] Ethylene-vinyl acetate copolymer (EVA) is a general-purpose polymer with good softness, high elasticity, tear resistance, impact resistance, stress cracking resistance and chemical stability. These excellent properties make EVA and its composites with other substances have great application value. EVA film is a new generation of green and environmentally friendly degradable material, which is biodegradable and will not cause harm to the environment when discarded or burned. EVA film is now widely used in solar photovoltaic module packaging, greenhouse film, food packaging, special packaging for medical and medicinal materials, etc. However, due to the low strength of EVA film, high water vapor permeability and water absorption rate, and poor weather resistance, long-term exposure to the outdoors or in a humid environment will cause water vapor to penetrate, resulting in film atomization, thereby limiting the application of EVA film in barrier properties.

[0003] At present, the barrier properties of EVA films are generally improved by adding organic clay, rectorite, nanofibers, or melt blending with other high barrier polymers in the EVA matrix. However, to achieve the required barrier properties, a large amount of fillers are usually required, which will inevitably have an adverse effect on other properties of EVA. In addition, some EVA manufacturers add hydrophobic polyolefin materials to EVA to enhance the water barrier rate, but the effect is not ideal, because the melting point of polyolefin is higher than that of EVA, so it is difficult to disperse evenly in EVA at low processing temperatures. Summary of the invention

[0004] The purpose of this application is to construct an EVA graphene composite film and a preparation method thereof, which has high water vapor barrier and electrical resistance properties, and the preparation process is simple and low-cost, which is conducive to large-scale industrial production.

[0005] In a first aspect, the present application provides a method for preparing an EVA graphene composite film, comprising:

[0006] Amino modification of graphene oxide: adding organic amine to the graphene oxide dispersion to react for a period of time, washing and drying to obtain modified graphene oxide;

[0007] Titanate modification: Modified titanate is obtained by intercalating carbonate with organic matter;

[0008] Preparation of EVA graphene outer film: EVA, graphene and the modified titanate are mixed and hot-pressed into a film to obtain the EVA graphene outer film;

[0009] Preparation of EVA graphene inner film: EVA, the modified graphene oxide and the initiator are fed into an open mill for rough mixing; after the open milling is completed, they are placed in a twin-screw extruder for blending and extrusion, and then hot-pressed into a film to obtain the EVA graphene inner film;

[0010] Preparation of EVA graphene composite film: overlapping and hot-pressing the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence to obtain the EVA graphene composite film.

[0011] In some embodiments, the step of aminated modification of graphene oxide includes: mixing a graphene oxide dispersion and adding a dodecyltrimethylammonium bromide solution and ultrasonically dispersing the mixture, then separating the solid from the liquid to obtain a solid, dispersing the solid and a polyamine in a solvent, ultrasonically dispersing the solid and heating the mixture to 40 to 60° C., reacting the mixture for 1 to 4 hours, and washing and drying the mixture to obtain modified graphene oxide.

[0012] In some embodiments, the mass ratio of the graphene, the dodecyltrimethylammonium bromide and the polyvalent organic amine is 1:(1.5-2.5):(1.5-2.5).

[0013] In some embodiments, the organic amine is selected from at least one of ethylenediamine, p-phenylenediamine, and diethylenetriamine.

[0014] In some embodiments, the solvent is selected from at least one of ethanol, tetrahydrofuran, acetone, formamide, and N,N-dimethylformamide.

[0015] In some embodiments, the titanate modification step includes: dispersing titanate and organic matter in a solvent, stirring and reacting at a temperature of 70 to 90° C. for 20 to 40 minutes to obtain the modified titanate.

[0016] In some embodiments, the titanate is selected from at least one of potassium titanate, sodium iron titanate, and potassium magnesium titanate;

[0017] The organic matter is selected from at least one of oleic acid and stearic acid.

[0018] In some embodiments, the organic matter is selected from at least one of oleic acid and stearic acid.

[0019] In some embodiments, the steps of preparing the EVA graphene outer film include: mixing EVA, graphene, and the modified titanate in a ratio of 8: (0.004-0.006): (0.008-0.015), and hot pressing at a temperature of 100-120°C and a pressure of 5-10MPa to obtain an EVA graphene outer film with a thickness of 0.1-0.2mm.

[0020] In some embodiments, the preparation steps of the EVA graphene inner membrane include: preparation of the EVA graphene inner membrane: EVA, the modified graphene oxide, and the initiator are mixed in a ratio of 1: (0.005-0.05): (0.0005-0.001) and fed into an open mill, and roughly mixed at 70-90° C. for 1.3-3 hours; after the open mill is completed, it is placed in a twin-screw extruder at a temperature of 80-100° C. for co-extrusion, and then hot-pressed at a temperature of 100-150° C. and a pressure of 5-10 MPa to obtain an EVA graphene inner membrane with a thickness of 0.1-0.2 mm.

[0021] In some embodiments, the initiator is an organic peroxide.

[0022] In some embodiments, the organic peroxide includes a mixture of one or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 4,4-di(tert-amylperoxy)butyl valerate, tert-butyl peroxy-2-ethylhexyl carbonate, and 3,3-di(tert-butylperoxy)hexyl butyrate.

[0023] In some embodiments, the preparation steps of the EVA graphene composite film include: overlapping the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence, and hot-pressing and compounding them at a temperature of 100-120° C. and a pressure of 5-10 MPa to obtain the EVA graphene composite film.

[0024] In a second aspect, the present application provides an EVA graphene composite film prepared by the preparation method described in any one of the first aspects.

[0025] Compared with the prior art, the above solution of the present application can at least achieve the following advantages:

[0026] (1) By modifying graphene with amino groups, free acidic molecules can be effectively absorbed; the epoxy functional groups on the surface of graphene oxide can be used to achieve in-situ grafting of EVA under the action of an initiator, thereby enhancing the bonding force between graphene oxide and the EVA matrix; in addition, a physical barrier layer of the EVA film is formed by the graphene sheet, and the hydrophobic property of titanate is used to enhance the water barrier property of the film, thereby effectively reducing the water vapor permeability of the EVA film; in addition, the volume resistivity of the composite film can also be increased.

[0027] (2) The graphene EVA composite film can be prepared simply and efficiently, the method is simple and feasible, and it is easy to industrialize. DETAILED DESCRIPTION

[0028] The present application provides a method for preparing an EVA graphene composite film, comprising:

[0029] S110 Amino modification of graphene oxide: Add organic amine to the graphene oxide dispersion and react for a period of time, then wash and dry to obtain modified graphene oxide.

[0030] Optionally, the step of aminated modification of graphene oxide includes: mixing a graphene oxide dispersion and a dodecyltrimethylammonium bromide solution and performing ultrasonic dispersion, then performing solid-liquid separation to obtain a solid, dispersing the solid and a polybasic organic amine in a solvent, ultrasonically dispersing and heating to 40 to 60° C., reacting for 1 to 4 hours, and obtaining modified graphene oxide after washing and drying.

[0031] Furthermore, the mass ratio of the graphene, the dodecyltrimethylammonium bromide and the polyvalent organic amine is 1:(1.5-2.5):(1.5-2.5). The organic amine is selected from at least one of ethylenediamine, p-phenylenediamine and diethylenetriamine. The solvent is selected from at least one of ethanol, tetrahydrofuran, acetone, formamide and N,N-dimethylformamide.

[0032] S120 titanate modification: modified titanate is obtained by intercalating carbonate with organic matter.

[0033] Optionally, the titanate modification step includes: dispersing carbonate and organic matter in a solvent, stirring and reacting at a temperature of 70 to 90° C. for 20 to 40 minutes to obtain the modified carbonate.

[0034] Furthermore, the carbonate is selected from at least one of potassium titanate, sodium iron titanate, and potassium magnesium titanate. The organic matter is selected from at least one of oleic acid and stearic acid.

[0035] S130 Preparation of EVA graphene outer film: EVA, graphene and the modified titanate are mixed and hot-pressed into a film to obtain the EVA graphene outer film.

[0036] Optionally, the step of preparing the EVA graphene outer film includes: mixing EVA, graphene and the modified titanate in the ratio of 8: (0.004-0.006): (0.008-0.015), hot pressing at a temperature of 100-120° C. and a pressure of 5-10 MPa to obtain an EVA graphene outer film with a thickness of 0.1-0.2 mm.

[0037] Preparation of S140 EVA graphene inner film: EVA, the modified graphene oxide and the initiator are fed into an open mill for rough mixing; after the open milling is completed, they are placed in a twin-screw extruder for blending and extrusion, and then hot-pressed into a film to obtain the EVA graphene inner film.

[0038] Optionally, the preparation steps of the EVA graphene inner membrane include: preparation of the EVA graphene inner membrane: EVA, the modified graphene oxide, and the initiator are mixed in a ratio of 1: (0.005-0.05): (0.0005-0.001), and fed into an open mill, and roughly mixed at 70-90° C. for 1.3-3 hours; after the open mill is completed, the mixture is placed in a twin-screw extruder at a temperature of 80-100° C. for co-extrusion, and then hot-pressed at a temperature of 100-150° C. and a pressure of 5-10 MPa to obtain an EVA graphene inner membrane with a thickness of 0.1-0.2 mm.

[0039] Furthermore, the initiator is an organic peroxide, which includes a mixture of one or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane, 4,4-di(tert-amyl peroxy) valerate n-butyl ester, tert-butyl peroxy-2-ethylhexyl carbonate, and 3,3-di(tert-butyl peroxy) butyrate.

[0040] S150 Preparation of EVA graphene composite film: overlapping and hot-pressing the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence to obtain the EVA graphene composite film.

[0041] Optionally, the preparation step of the EVA graphene composite film includes: overlapping the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence, and hot-pressing and compounding them at a temperature of 100-120° C. and a pressure of 5-10 MPa to obtain the EVA graphene composite film.

[0042] In a second aspect, the present application provides an EVA graphene composite film prepared by the preparation method described in any one of the first aspects.

[0043] In this application, graphene oxide is a two-dimensional material mainly composed of carbon atoms. At the same time, due to the rich functional groups on the surface, it has good compatibility with polymers, and thus has great development prospects in the field of high barrier applications. For EVA, -O-CO- is the main reason for hindering the reduction of water vapor permeation. Water vapor can not only cause the ester group -O-CO- in the EVA film to hydrolyze to form free acidic molecules, but also cause yellowing and induce snail lines and other phenomena.

[0044] Therefore, the present application not only can effectively absorb free acidic molecules but also can utilize the epoxy functional groups on the surface of graphene oxide to realize in-situ grafting of EVA under the action of an initiator, thereby enhancing the bonding force between graphene oxide and the EVA matrix; in addition, a physical barrier layer of the EVA film is formed by the graphene sheet layer, and the surface modification of the hydrophobic titanate is performed, thereby effectively reducing the water vapor permeability of the EVA film; in addition, due to the aforementioned modification, the volume resistivity of the EVA graphene composite film can also be increased.

[0045] The present application can be better understood according to the following embodiments. However, it is easy for those skilled in the art to understand that the contents described in the embodiments are only used to illustrate the present application, and should not and will not limit the present application described in detail in the claims.

[0046] Example

[0047] A method for preparing an EVA graphene composite film, comprising:

[0048] (1) 1 g of graphene oxide was added to 2 L of water, and 1 g of CTAB (dodecyltrimethylammonium bromide) was dispersed in 2 L of ethanol to dissolve. Then, the graphene oxide was added to the ethanol solution of CTAB under high-speed stirring and ultrasonically dispersed for 20 min. The flocculants were separated by centrifugation, and the product was repeatedly washed with ethanol until the product was no longer turbid; p-phenylenediamine was dissolved in 1 L of solvent ethanol, ultrasonically dispersed for 20 min, and then heated to 55 ° C for reaction for 3 h. The product was then washed several times with the same solvent and dried to obtain modified graphene. The amount of p-phenylenediamine added is shown in Table 1.

[0049] (2) Sodium iron titanate and oleic acid are dispersed in ethanol, and stirred for reaction at 80° C. for 30 min to obtain modified sodium iron titanate.

[0050] (3) EVA, graphene, and modified sodium iron titanate were mixed in a ratio of 8:0.005:0.01, and hot-pressed at a temperature of 100° C. and a pressure of 10 MPa for 40 min to obtain an EVA graphene outer film with a thickness of 0.2 mm.

[0051] (4) EVA (VA content is 28%) is fed into an open mill for refining at a temperature of 80°C. After the EVA forms a film on the roller, modified graphene and initiator (diisopropylbenzene peroxide) are dripped onto the film and spread on the film with a scraper. After the film is dry, the rubber is cut and turned over continuously. After rough mixing in the open mill, the mixture is placed in a twin-screw extruder for co-extrusion. The screw temperature is set to 100°C for co-extrusion. Then, hot pressing is performed at a temperature of 150°C and a pressure of 10MPa to obtain an EVA graphene inner film with a thickness of 0.1mm. The specific addition amounts of EVA masterbatch, modified graphene oxide, and initiator are shown in Table 1.

[0052] (5) Overlap the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence and place them in a 0.5 mm mold. Set the film forming pressure to 10 MPa, the film forming temperature to 100 ° C, and hot press for 40 minutes. After the temperature naturally drops to room temperature, release the pressure and demold to obtain an EVA graphene composite film.

[0053] The water vapor transmission test was measured according to the standard "GB 21529 Determination of water vapor transmission rate of plastic film and sheet - Electrolytic sensing method", and the volume resistivity was measured according to GB / T1410-2006. The results are shown in Table 1.

[0054] Table 1 Preparation process and properties of composite membranes

[0055]

[0056]

[0057] As can be seen from Table 1, the EVA graphene composite film provided in the present application has better water vapor barrier properties and increased volume resistivity, indicating that it has excellent water vapor and electrical resistance properties.

[0058] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application claimed for protection, but only represents selected embodiments of the present application.

Claims

1. A method for preparing an EVA graphene composite film, characterized in that: include: Amino modification of graphene oxide: adding organic amine to the graphene oxide dispersion to react for a period of time, washing and drying to obtain modified graphene oxide; Titanate modification: Modified titanate is obtained by intercalating carbonate with organic matter; Preparation of EVA graphene outer film: EVA, graphene and the modified titanate are mixed and hot-pressed into a film to obtain the EVA graphene outer film; Preparation of EVA graphene inner film: EVA, the modified graphene oxide and the initiator are fed into an open mill for rough mixing; after the open milling is completed, they are placed in a twin-screw extruder for blending and extrusion, and then hot-pressed into a film to obtain the EVA graphene inner film; Preparation of EVA graphene composite film: overlapping and hot-pressing the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence to obtain the EVA graphene composite film.

2. The preparation method according to claim 1, characterized in that: The step of aminated modification of graphene oxide comprises: mixing a graphene oxide dispersion liquid and a dodecyltrimethylammonium bromide solution and performing ultrasonic dispersion, then performing solid-liquid separation to obtain a solid, dispersing the solid and a polybasic organic amine in a solvent, performing ultrasonic dispersion and heating to 40 to 60° C., reacting for 1 to 4 hours, and obtaining modified graphene oxide after washing and drying.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the graphene, the dodecyltrimethylammonium bromide and the polyvalent organic amine is 1:(1.5-2.5):(1.5-2.5); Or / and, the organic amine is selected from at least one of ethylenediamine, p-phenylenediamine and diethylenetriamine; Or / and, the solvent is selected from at least one of ethanol, tetrahydrofuran, acetone, formamide, and N,N-dimethylformamide.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The titanate modification step includes: dispersing titanate and organic matter in a solvent, stirring and reacting at a temperature of 70 to 90° C. for 20 to 40 minutes to obtain the modified titanate.

5. The preparation method according to claim 4, characterized in that: The titanate is selected from at least one of potassium titanate, sodium iron titanate, and potassium magnesium titanate; The organic matter is selected from at least one of oleic acid and stearic acid.

6. The preparation method according to any one of claims 1 to 3, characterized in that The steps of preparing the EVA graphene outer film include: mixing EVA, graphene and the modified titanate according to 8: (0.004-0.006): (0.008-0.015), hot pressing at a temperature of 100-120° C. and a pressure of 5-10 MPa to obtain an EVA graphene outer film with a thickness of 0.1-0.2 mm; The preparation steps of the EVA graphene inner film include: mixing EVA, the modified graphene oxide and the initiator in a ratio of 1:(0.005-0.05):(0.0005-0.001), feeding into an open mill, and roughly mixing at 70-90° C. for 1.3-3 hours; after the open milling is completed, placing in a twin-screw extruder at a temperature of 80-100° C. for co-extrusion, and then hot pressing at a temperature of 100-150° C. and a pressure of 5-10 MPa to obtain an EVA graphene inner film with a thickness of 0.1-0.2 mm.

7. The preparation method according to claim 6, characterized in that: The initiator is an organic peroxide.

8. The preparation method according to claim 7, characterized in that: The organic peroxide includes a mixture of one or more of diisopropylbenzene peroxide, di-tert-butyl peroxide, diisopropylbenzene hydroperoxide, 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane, 4,4-di(tert-amylperoxy)butyl valerate, tert-butyl peroxy-2-ethylhexyl carbonate, and 3,3-di(tert-butylperoxy)hexyl butyrate.

9. The preparation method according to any one of claims 1 to 4, characterized in that: The preparation steps of the EVA graphene composite film include: overlapping the EVA graphene outer film, the EVA graphene inner film and the EVA graphene outer film in sequence, and hot-pressing and compounding them under the conditions of a temperature of 100-120° C. and a pressure of 5-10 MPa to obtain the EVA graphene composite film.

10. An EVA graphene composite film, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Vinyl polymer nano composite material containing polar side group and preparation method thereof

    CN108084615A

  • Gas barrier coating agent, gas barrier film and method for producing the same

    JP2017210515A

  • Multilayered resin molded body and method for manufacturing same

    US20130316159A1